SEASONAL MIGRATION IN THE HARVEST OF SUGARCANE IN BRAZIL: CHALLENGES FOR HUMAN RIGHTS AND SOCIAL JUSTICE - Alves de Oliveira, Rose (Revista Gênero e Interdisciplinaridade, 2024)
It is known that there are challenges faced by seasonal migrant workers in the harvest of sugarcane in Brazil, highlighting issues related to human rights and social justice. In this study, precarious working conditions, health impacts and limited access to fundamental labor rights faced by these workers are exploited. In addition, existing government policies and gaps in the legal protection of these workers are discussed, emphasizing the need for measures to promote a safer, more dignified and fair migration. There are also the following research questions that have moved the search in this study: What are the main causes of seasonal migration in sugarcane harvesting? What are the main challenges faced by workers? How is social justice impacted by migration? What policies and practices were innovative to protect rights? Thus, this study aimed to reflect on the theme of seasonal migration in the harvest of sugarcane and its implications for social justice and the human rights of these people. This study is a bibliographic revision of the narrative, qualitative type; which was built from the following steps: definition of the problem; Review planning; Choose databases; Definition of keywords; Selection of inclusion and exclusion criteria; Search in literature; Selection of studies and finally, critical analysis, which will allow a synthesis of the results found. Studies published in the last 10 years have been used on the subject, which have been organized in a single framework and compared in the textual discussion. Therefore, this article provided the reflection on this theme, verifying that the instability caused by migration can lead to problems in the family, educational, emotional, social, economic area, within others. It was possible to highlight that the fact that it seeks to develop programs that allow the creation of public policies that guarantee social justice, and minimization of social iniquities, are necessary.